Immunocompetence Index Performance of the IPB-D3 Candidate Line under Different Rearing Systems - Vianisa, Putri; Murtini, Sri; Furqon, Ahmad; Sumantri, Cece (Faculty of Animal Science, Universitas Brawijaya, 2025)
IPB-D3 chickens possess strong adaptive potential that enhances immune system performance and resilience, making them promising candidates for developing superior local breeds. However, their health and welfare are largely influenced by rearing methods, and no data are currently available on this topic. Therefore, this study aimed to assess the immunocompetence index of IPB-D3 chickens under different rearing systems by measuring IgY concentrations. A total of 90 IPB-D3 chickens were reared for 12 weeks; 30 samples were taken from each of the intensive and free-range groups for analysis. The observed variables included the environmental temperature and humidity measured in the morning, afternoon, and evening, as well as the IgY concentrations analysed via indirect ELISA. Blood samples from male and female chickens were collected separately. The data were statistically analysed via an independent t test with SPSS version 26. This study revealed that the daytime temperature and humidity were significantly affected (p < 0.05) by the rearing system but not by the morning or evening. The IgY concentrations did not differ significantly (p > 0.05) between the intensive (10.23 µg/mL) and free-range (9.91 µg/mL) systems. In the intensive system, male chickens had an IgY level of 11.38 µg/mL, and female chickens had an IgY level of 9.16 µg/mL; in the free-range system, male chickens had an IgY level of 9.18 µg/mL, and female chickens had an IgY level of 10.64 µg/mL. These results indicate that neither the rearing system nor sex significantly influences the immune response. This study revealed that both male and female IPB-D3 chickens present high and stable IgY concentrations across different rearing systems, reflecting good immunocompetence and adaptability, thereby supporting their potential as superior lines.